FREE JAZZ: PERFORMANCE STYLES IN THE EARLY AVANTGARDE JAZZ DIRECTION AND THEIR DEVELOPMENT DYNAMICS - Baxodir Fayziev (Modern American Journals, 2025)
The article analyzes the aesthetic, structural and performance characteristics of the Free Jazz - avant-garde jazz movement that emerged in the second half of the 20th century. The work of Ornette Coleman and Cecil Taylor, who were among the first to establish this movement, demonstrates the rejection of traditional rules of harmony, rhythm and form. The recognition of free jazz in the professional music field and its influence on the next generation of performing styles based on the work of John Coltrane are scientifically examined. Through musical analysis, the unlimited possibilities of free jazz in terms of material, texture, improvisation and timbre are studied.
Keywords: Free Jazz, avant-garde, improvisation, Ornette Coleman, John Coltrane, Cecil Taylor, modern performance, harmony, rhythm.